Chromogranin A deficiency attenuates tauopathy by altering epinephrine–alpha-adrenergic receptor signaling in PS19 mice - Suborno Jati; Daniel Munoz-Mayorga; Shandy Shahabi; Kechun Tang; Yuren Tao; Dennis W. Dickson; Irene Litvan; Gourisankar Ghosh; Sushil K. Mahata; Xu Chen (Nature Communications)
Abstract Metabolic disorders such as insulin resistance and hypertension are potential risk factors for aging and neurodegenerative diseases. These conditions are reversed in Chromogranin A (CgA) knockout (CgA-KO) mice. CgA is known to be associated with protein aggregates in the brains of neurodegenerative diseases including Alzheimer’s disease (AD). Here, we investigated the role of CgA in Tau pathogenesis in AD and corticobasal degeneration (CBD). CgA ablation in Tauopathy mice (PS19) (CgA-KO/PS19) reduced pathological Tau aggregation and spreading, extended lifespan, and improved cognitive function. Transcriptomic and metabolite analysis of mouse cortices revealed elevated alpha-1-adrenergic receptors (Adra1) expression and high Epinephrine (EPI) levels in PS19 mice compared to WT mice, mirroring observations in AD and CBD patients. CgA depletion in PS19 mice lowered cortical EPI levels and the expression of Adra1 back to normal. Treatment of WT hippocampal organotypic slice cultures with EPI or Adra1 agonist promoted, while an Adra1 antagonist inhibited Tau hyperphosphorylation and formation of neurofibrillary tangles, which is unaltered upon CgA depletion. These findings demonstrate the involvement of CgA in Tau pathogenesis and highlight the interplay between the EPI-Adra1 signaling pathway and CgA in Tauopathy.